Clinical Characteristics of Patients With Papilloma in the External Auditory Canal. (8th October 2020) - Luo, Wenwei; Wu, Jingfang; Peng, Kevin A.; Li, Qingzhong; Du, Qiang; Xu, Jianghong; Dai, Chunfu; Chi, Fanglu; Shu, Yilai
Abstract : Objectives: To determine the clinical characteristics of papilloma involving the external auditory canal (PEAC) in a region of China. Study design: A retrospective study. Methods: Demographics, manifestations, imaging results, histopathology, and treatment of 67 patients diagnosed with PEAC in a period of 6 years were analyzed at Shanghai Eye, Ear, Nose and Throat Hospital in China. Results: PEAC were encountered in patients between the ages of 12 and 82 years (mean 53.8 years). It was more prevalent in men (82%) than in women (18%) ( P < .05). The clinical presentation was usually a mass in EAC, aural fullness, and hearing loss. Otoscopic and radiological examination were used together for initial diagnosis and pretreatment planning. Unilateral involvement was more common than bilateral involvement ( P < .05). The average time between onset of first symptom and surgical resection and/or biopsy was 6.5 months (range, 0.25–60 months). All patients underwent gross total resection. In 5 patients, (7.5%) carcinoma was detected in the specimen. Fifteen patients (22%) had recurrence; recurrent tumors were detected after an average period of 10 months after surgery (range, 4–24 months). Conclusion: PEAC is largely a benign lesion with a low risk of malignancy. Optimal management is via gross total resection. However, the risk of recurrence is high, which motivates a need for long‐term monitoring. Level of Evidence: 4 Laryngoscope, 131:1132–1137, 2021